An Analysis of Political Allegory in Animal Farm by George Orwell - Zumi, Zumyati; Ulpia, Ulpia Rahim; Sari, Novita Sari; Khairunnisa, Khairunnisa; Abdul Syahid, Abdul Syahid (Darussalam English Journal (DEJ), 2025)
This study analyzes George Orwell’s Animal Farm as a political allegory that critiques totalitarian regimes and the corruption of revolutionary ideals. Using a qualitative descriptive-analytical approach, the research applies semiotic and discourse analysis to examine the symbolic elements and political messages embedded in the novel. The findings reveal that characters such as Napoleon, Snowball, and Boxer symbolize key figures and classes from the Russian Revolution and Stalinist era, highlighting Orwell’s critique of propaganda, ideological control, and exploitation. The study shows how Orwell employs satire and allegory to depict the manipulation of language and truth, reflecting broader political realities both historically and in contemporary society. The novel serves as a cautionary tale about the dangers of unchecked power and remains highly relevant in today’s political climate.